Promoting Social and Emotional Learning in Physical Education. Issue 4 (4th May 2018) - Ciotto, Carol M.; Gagnon, Amy G.
Abstract : A positive social and emotional climate in the classroom allows for students to communicate and interact in beneficial ways. Positive peer interactions are necessary for academic and career success, as well as for success in physical education. This article provides physical educators with principles and guidelines for developing, implementing and assessing effective strategies for promoting social and emotional learning within their programs. The five core competencies of social and emotional learning as described by the Collaborative for Academic, Social and Emotional Learning's (CASEL) will be discussed.